Dimensions of bilingual education program implementation in schools serving linguistically minoritized students in the Czech-Polish border region - Hopkins, Megan; Nowak-Żółty, Edyta; Kurowska-Pysz, Joanna; Szyszka, Michał (Frontiers in Education, 2023)
A core challenge for the implementation of bilingual programs is ensuring that linguistically minoritized students have equitable access to instruction that honors and values their linguistic and cultural assets and strengths. To understand how leaders of bilingual programs might address this challenge, this study sought to identify dimensions of program implementation in bilingual schools serving Polish minorities in the Zaolzie region on the Czech Republic side of the Czech-Polish border. Analysis of surveys collected from 123 teachers, interviews with five community leaders, and observations of community and classroom settings highlighted four dimensions of program implementation: a) program structure and alignment; b) culturally and linguistically responsive instruction; c) staff quality and professional learning; and d) family engagement and community support. Findings also revealed how a network of community-based organizations partnered with schools and families in ways that supported each dimension and facilitated integration across dimensions. Implications for leaders and researchers in bilingual schools are discussed.